2021
DOI: 10.1089/dna.2020.6338
|View full text |Cite
|
Sign up to set email alerts
|

Lentinan Attenuated the PM2.5 Exposure-Induced Inflammatory Response, Epithelial–Mesenchymal Transition and Migration by Inhibiting the PVT1/miR-199a-5p/caveolin1 Pathway in Lung Cancer

Abstract: PM2.5 plays an important role in the physiological and pathological progression of lung cancer. Lentinan exerts antitumor activity in many kinds of human cancers. Plasmacytoma variant translocation 1 (PVT1) exerts antitumor activity in many kinds of human cancers. However, the role and underlying molecular mechanism of PVT1 in the role of lentinan in PM2.5-exposed lung cancer are still largely unknown. Our study confirmed that PM2.5 exposure induced the production of inflammatory factors, epithelial-mesenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…In this study, we, for the first time, attempted to screen potential lncRNAs and pseudogenes associated with CNT-induced lung carcinogenesis based on a comprehensive bioinformatics analysis of microarray data of lung cells directly exposed to CNTs without other influencing factors (GSE41178 and GSE561040) and sequencing (TCGA), proteomics (CPTAC) and immunohistochemical data (HPA) of lung cancer patients. Similar to the studies of PM2.5 [ 35 ], nickel [ 36 ] and cadmium [ 37 ] exposure, we also identified that the upregulation of PVT1 and downregulation of MEG3 contributed to the acquisition of tumorigenic phenotypes of human SAECs after CNT exposure. An increase in the expression level of lncRNA ARHGAP5-AS1 and decreases in the expression levels of lncRNA LINC00174, pseudogene MT1JP, MT1L, RPL23AP64, ZNF826P and TMEM198B were newly identified mechanisms in our study to explain the carcinogenic effects of CNTs.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this study, we, for the first time, attempted to screen potential lncRNAs and pseudogenes associated with CNT-induced lung carcinogenesis based on a comprehensive bioinformatics analysis of microarray data of lung cells directly exposed to CNTs without other influencing factors (GSE41178 and GSE561040) and sequencing (TCGA), proteomics (CPTAC) and immunohistochemical data (HPA) of lung cancer patients. Similar to the studies of PM2.5 [ 35 ], nickel [ 36 ] and cadmium [ 37 ] exposure, we also identified that the upregulation of PVT1 and downregulation of MEG3 contributed to the acquisition of tumorigenic phenotypes of human SAECs after CNT exposure. An increase in the expression level of lncRNA ARHGAP5-AS1 and decreases in the expression levels of lncRNA LINC00174, pseudogene MT1JP, MT1L, RPL23AP64, ZNF826P and TMEM198B were newly identified mechanisms in our study to explain the carcinogenic effects of CNTs.…”
Section: Discussionsupporting
confidence: 87%
“…In recent decades, mounting evidence has supported the idea that environmental pollutants (such as PM2.5 [ 33 , 34 , 35 ], nickel [ 36 ] and cadmium [ 37 , 38 ]) promote the malignant transformation of lung epithelial cells by changing the expression levels of ncRNAs. Dysregulation of ncRNA expression levels was also revealed to be a novel paradigm for interpretation of the toxicology of various nanoparticles [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ning et al [99] found 13 deregulated miRNAs related to lung cancer in the serum of mice inhaled PM 2.5 for 8 weeks. Moreover, miR-32, miR-582-5p, and miR-199a-5p participate in PM 2.5 -induced EMT and CSC processes, suggesting that miRNAs might be potential targets for lung cancer therapy [94,95,100]. We found that melatonin has an anti-tumor effect by reducing oxidative damage [101].…”
Section: Lung Cancermentioning
confidence: 73%
“…Over recent years, researchers have attempted to prevent and control the cellular and organ damage caused by PM2.5. Some researchers have shown that some natural compounds and traditional Chinese medicines can protect the cell and organ damage induced by PM2.5 both in vitro and in vivo , including calycosin [ 17 ], isovitexin [ 18 ], astaxanthin [ 19 ], curcumin [ 20 ], astragalus [ 21 ], codonopsis pilosula [ 21 ], ophiopogonin [ 22 ], triptolide [ 23 ], astragaloside IV [ 24 ], resveratrol [ 25 ], and lentinan [ 26 ]. All of these studies were carried out in vivo ; drugs were administered systematically, by either oral or injection routes.…”
Section: Discussionmentioning
confidence: 99%